Drought Stress and Root-Associated Bacterial Communities - Naylor, Dan; Coleman-Derr, Devin (Frontiers in Plant Science, 2018)
Root-associated bacterial communities play a vital role in maintaining health of the plant host. These communities exist in complex relationships, where composition and abundance of community members is dependent on a number of factors such as local soil chemistry, plant genotype and phenotype, and perturbations in the surrounding abiotic environment. One common perturbation, drought, has been shown to have drastic effects on bacterial communities, yet little is understood about the underlying causes behind observed shifts in microbial abundance. As drought may affect root bacterial communities both directly by modulating moisture availability, as well as indirectly by altering soil chemistry and plant phenotypes, we provide a synthesis of observed trends in recent studies and discuss possible directions for future research that we hope will provide for more knowledgeable predictions about community responses to future drought events.